Conotoxins from venome of cone snails (Conus) and it’s application for pharmaceutical medicine - Thao, Le Thi Bich; Huyen, Bui Thi; Binh, Doan Viet; Kim Dung, Nguyen Thi; Minh Phuong, Nguyen Thi; Chi, Do Huu; Nghi, Bui Quang; Nhi, Nguyen Bich; Chi, Phan Van (Academia Journal of Biology, 2016)
Conotoxins in venoms of marine cone snails  are structural diversity, rich disulfide-bridges that selective block of ion channel voltages or receptors, therefore it is used for development of analgesic drugs. In this paper, we investigated conotoxins from venoms of eight cone snails  of the genus Conus in Vietnam by using a nano-liquid chromatography linked mass spectrometry. For medical application, the recombinant ω-conotoxin MVIIA was expressed in E. coli and determined analgesic activity by testing on the mice. As the results, the conotoxins were identified in venoms of eight conus mainly belong to O, M, A super families. In addition, many small peptides were determinated, however these databases are not clear due to reference of DNA and protein databases is deficient. Recombinant MVIIA (CTX) was expressed in the fusion with thioredoxin in molecular weight of 20.5 kDa (Trx-CTX) and the original CTX peptide was purified in size of below 3 kDa after removing thioredoxin and his tag. Both of CTX peptide and Trx-CTX fusion protein showed an analgesic activity when compared to lidocaine and morphine. Hence, these recombinant proteins could be potential drugs for effective analgesic treatment.